ANALISIS PEMANFAATAN FUNGSI ATM TERHADAP PENINGKATAN PELAYANAN NASABAH PADA PT. BCA TBK MEDAN - Lidia Yunita (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2016)
The banking sector is now very advanced with the development of science and technology human beings. Human life is very mobile, it must demand a lifestyle that is practical and fast. BCA Bank is a private bank that is considered quite good, because it is the biggest and most reliable transactional bank in Indonesia. In general, the function ATM that is to make transactions of cash withdrawal as: to withdraw cash 24 hours a day, the customer does not depend on the hours of service of the bank, can be used as a debit card, free long queues, save time, because it no longer follow administrative procedures, more easily achieved because it is available in various strategic locationsBased on the research that has been done, the problems faced by PT. BCA Tbk is sebgai follows: